Selective Sequential Cross-Coupling Reactions on Imidazole towards Neurodazine and Analogues - Recnik, Lisa-Maria; Abd El Hameid, Mohammed; Haider, Maximilian; Schnürch, Michael; Mihovilovic, Marko D. (Synthesis, 2013)
Polysubstituted imidazoles represent a common structural motif in bioactive molecules. A modular and flexible strategy towards 2,4,5-triarylated imidazoles is reported applying a Suzuki–Miyaura cross-coupling protocol. Employing 1-protected 2,4,5-tribromoimidazole as starting material, both stepwise and one-pot protocols towards the title compounds are disclosed. The utility of the approach was demonstrated by synthesizing neurodazine, a biologically active molecule affecting neuronal cell differentiation.
Keywords: heterocycles; cross-coupling; palladium; regioselectivity; homogeneous catalysis